Determination of streptomycin residues in imported and locally produced honey in Kosovo - Adem Rama; Imer Haziri; Iliriana Miftari; Afërdita Zuka; Blend Zhuri; Arlind Latifi; Drilon Hasani; Fatgzim Latifi (International Journal of Food Contamination, 2022)
Abstract Although bee honey is considered an essential and healthy food for humans, honey can be affected by various contaminants, such as antibiotics, that can cause health problems for consumers. The objective of this study was to assess the occurrence of streptomycin residues in locally produced and imported bee honey, which was collected in 2017 from individual apiaries and retail markets in six different regions of Kosovo. In the present study, 155 bee honey samples were qualitatively screened by the enzyme-linked immunosorbent assay (ELISA) method using an I'screen STREPTO test kit (Tecna S. r. L., Trieste, Italy) as a simple and fast method. Descriptive statistics were used to outline the essential characteristics of the sample and mass; 29% of samples were contaminated with streptomycin at concentrations between 2.1-9.3 ug/kg, while 71% of the samples were found to be negative for streptomycin. Most of the samples with streptomycin residues were from the Ferizaj and Prizren regions. Based on these results, competent authorities should establish and maintain programs to continuously monitor honey to ensure that consumers in Kosovo receive risk-free honey. In addition, there is a pressing need for additional research to accurately assess other aspects of this problem and identify effective corrective actions that will reduce contaminants in bee honey.